The Effect Of Local Own-Source Revenue And Balancing Funds On The Human Development Index (Empirical Study On Regencies/Cities In West Java Province For The Period 2017–2022) - Anggadanta, Rullyansyah (Journal Research of Social Science, Economics, and Management, 2025)
This study aims to examine the effect of local revenue, balancing funds partially on the human development index. The population in this study were all district/city governments in West Java province. The total population was 27 district/city governments and all of them were used as samples in this study. The data used in this study were secondary data from human development index reports and regional government budget realization reports for districts/cities in West Java province for the 2017-2022 period. The analysis method used was panel data regression analysis with eviews 13 software. The results showed that local revenue and balancing funds had a positive effect on the human development index partially.